Advancing life projects: South African students explain why they come to FET colleges - Powell, Lesley; McGrath, Simon (University of Malaya Press, 2014)
VET policy in South Africa is based on a set of assumptions regarding the identity of learners and why learners are in public further education and training (FET) colleges. These assumptions reflect an international orthodoxy about the centrality of employability that is located within what Giddens (1994) has described as “productivism”, a view that reduces the lifeworld to the economic sphere. Through exploring the stories of a group of South African public FET college learners regarding their reasons for choosing FET colleges, this paper shows that VET is valued by these students for a range of reasons. These include preparation for the world of work, but also a desire to improve their ability to contribute to their communities and their families; raise their self-esteem; and expand their future life possibilities. Thus, the paper advances the largely hitherto theoretical critique of productivist VET accounts by offering empirical evidence of counter-narratives.